Understand electronics - Bishop, O. N. (Owen Neville) (Newnes/Butterworth-Heinemann, 2001)
In Understand Electronics, Owen Bishop covers the basics needed in all the main areas of electronics with a jargon-free, informative style, and numerous illustrations. An essential book for the newcomer to electronics, this highly practical guide provides a thorough introduction to practical electronics and the basic principles of electronic components and circuitry. Owen Bishop, a leading international electronics author, takes a step-by-step approach, employing the minimum of mathematics, to create a text that is ideal for the student or enthusiast who has little previous knowledge of the subject area but wishes to find out more. The new edition has been thoroughly updated throughout, with many new illustrations and coverage of recent advances in electronics, including a chapter on microcontrollers - the simple programmable devices that are transforming electronics project work. A new section on test equipment reinforces the practical emphasis of the book. A practical guide made highly accessible through clear explanations and numerous illustrations Assumes little previous knowledge of the subject area or mathematical background Covers the basics needed in all the main areas of electronics.